1956
DOI: 10.1063/1.1743185
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Density of the Liquid System TNT-Picric Acid and Four Related Pure Materials

Abstract: The viscosity and density of the system TNT-picric acid and four related susbstances have been investigated over a range of temperature which included both normal and supercooled liquids. The temperaturedependence of viscosity was found to be best represented by a continuous exponential function of the type '1=A exp(B/T +C/P), which yielded a good fit to the data even well into the supercooled region. Density in each case was found to vary linearly with temperature across the entire range. The results are inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
4
13
0
Order By: Relevance
“…We recently completed a study into the flow properties of molten 2,4,6-trinitrotoluene (TNT) and have found our values for the viscosity of molten T N T are in disagreement with those published [1,2]. We intend to publish a fuller account in the near future.…”
Section: Introductionmentioning
confidence: 48%
See 3 more Smart Citations
“…We recently completed a study into the flow properties of molten 2,4,6-trinitrotoluene (TNT) and have found our values for the viscosity of molten T N T are in disagreement with those published [1,2]. We intend to publish a fuller account in the near future.…”
Section: Introductionmentioning
confidence: 48%
“…The variation of Moore et al [1] data from linearity is evidence for an inverse temperature dependence of the flow activation energy which in itself is a very interesting phenomenon. We were most concerned that our results varied widely from values calculated from the Moore et al [1] equation. A temperature inaccuracy of approximately 3 °C would be required to cause our values to overlap, which was highly unlikely.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, because of the low density and low viscosity of DNAN [12][13][14], solid-liquid phase dislocations may appear during processing of a composite when using DNAN as the continuous phase, which will induce degradation of the solid phase, and affect the mechanical properties of the energetic composite, leading to weak dimensional stability, poor toughness and high brittleness [15][16][17]. Molecular simulations and mechanical tests of TNT and DNAN show that the compressive strength, tensile strength, shear strength and plastic deformation of DNAN are all lower than those of TNT, thus DNAN is more prone to brittle fracturing compared with TNT [18].…”
mentioning
confidence: 99%